The Influence of Profitability, Liquidity, and Solvency on the Share Prices of Kompas 100: Evidence from Non-Financial Companies - Purba, Acabelina Fine Claudia; Silaban, Barnabas Tridig (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study examines and analyzes the impact of profitability, liquidity, and solvency on the share price. Non-financial companies, becoming the KOMPAS 100 index constituents between 2019 and 2022, perform as the population. Furthermore, this study uses purposive sampling to take them as the samples. Mentioning the criteria, 58 associated firms are obtainable. Hence, 232 observations exist. After that, this study analyzes the data based on multiple linear regression and its classical assumption tests. After removing outliers, the total observations become 188. Based on the statistical analysis of 188 observations, this study reveals that the stock price is positively influenced by profitability and solvency but negatively affected by liquidity.